Minimal Clinically Important Difference of the Standardized Cosmesis and Health Nasal Outcomes Survey. (9th March 2019) - Kandathil, Cherian K; Saltychev, Mikhail; Abdelwahab, Mohamed; Spataro, Emily A; Moubayed, Sami P; Most, Sam P
Abstract: Background: The minimal clinically important difference (MCID) for the Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) has not been determined. Objectives: The authors sought to define the MCID for both domains of the SCHNOS questionnaire. Methods: This prospective cohort study included patients who underwent functional, cosmetic, or combined rhinoplasty operation from June 2017 to June 2018 at a tertiary referral center. The average preoperative, postoperative, and change in scores were calculated for the nasal obstruction symptom evaluation scale (NOSE) and SCHNOS. Anchor-based MCIDs were estimated for both SCHNOS subscales to define change in obstruction and cosmesis perceived after the rhinoplasty. Results: Eighty-seven patients (69% women, 31% males) with a mean age (standard deviation [SD]) of 38 years (14.7) at the time of surgery were included. The mean postoperative follow-up period (SD) was 145 days (117). The mean preoperative score (SD) for the NOSE was 52 (32), SCHNOS for nasal obstruction (SCHNOS-O) score was 55 (33), and SCHNOS for nasal cosmesis (SCHNOS-C) score was 50 (26) points. Postoperatively, the NOSE score was 23 (22), SCHNOS-O score was 24 (23), and SCHNOS-C score was 13 (18) points. The mean change in scores (SD) for NOSE, SCHNOS-O, and SCHNOS-C was −29 (37), −31 (38), and −37 (28), respectively. The calculated MCID for SCHNOS-O was 26 (16) and for SCHNOS-C was 22 (15) points. The MCID for NOSE was 24 (13) points. A sensitivity test for the patients with a follow-up ≥3 months showed only slightly different MCID estimates: 28 (17) for SCHNOS-O, 18 (13) for SCHNOS-C, and 24 (15) points for NOSE. Conclusions: For the obstruction domain SCHNOS-O, the MCID was 28 points. For the cosmetic domain SCHNOS-C, the MCID was 18 points.